Application of gemoy interactive model to improve adolescents' compliance in controlling blood pressure in Tambang Sub-District - Safitri, Yenny; Nurman, Muhammad; Widiyanto, Juli; Yarnita, Yeni; Juwita, Dewi Sulastri (Universitas Aisyah Pringsewu, 2024)
Background: Hypertension among adolescents is an emerging public health concern, especially in rural Indonesian settings such as Tambang Sub-District. Objectives: This study investigates the effectiveness of the GEMOY Interactive Model in increasing adolescents' compliance with blood pressure control through an engaging, web-based platform. Method: A quasi-experimental design with pre- and post-test control groups was conducted among 80 adolescents aged 15–18 years. Result: The intervention group received access to the GEMOY application which includes gamified health education, peer support forums, and self-monitoring features, while the control group received standard education. The results showed a significant improvement in knowledge, self-efficacy, and behavioral compliance (p0.05) among the intervention group. Conclusion: These findings support the use of interactive digital health models in hypertension prevention among youth.